TEKNIK PENERJEMAHAN ELIPSIS NOMINA DALAM NOVEL ANNE OF GREEN GABLES KARYA LUCY MONTGOMERY DARI BAHASA INGGRIS KE DALAM BAHASA INDONESIA - Rita Amalia Roostina (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2018)
This research is intended to analyse translation technic of noun eliptic at Anne of Green Gables Novel, a work of Lucy Montgomery, English to Indonesian. This research uses descriptive qualitative approach, further uses inductive content analytical method. Validity on this research are verified by its credibility, trasnferabilty, dependability and confirmability. This research reveals 127 kinds of noun eliptics in which 69 deictic, 46 numerative and 12 ephitets eliptics. Furthermore, these numbers of elliptical are used three category of translation techniques. There are 5 types of single translation, 3 types of double translation and 2 types of triple translation. These findings would be helpful for education especially teachers and translators. Key Words: translation, treanslation techniques, elliptical noun.